Manipulating the Stacking of Triplet Chromophores in the Crystal Form for Ultralong Organic Phosphorescence. (28th August 2019) - Gan, Nan; Wang, Xuan; Ma, Huili; Lv, Anqi; Wang, He; Wang, Qian; Gu, Mingxing; Cai, Suzhi; Zhang, Yanyun; Fu, Lishun; Zhang, Meng; Dong, Chaomin; et al.
Abstract: Provided here is evidence showing that the stacking between triplet chromophores plays a critical role in ultralong organic phosphorescence (UOP) generation within a crystal. By varying the structure of a functional unit, and different on‐off UOP behavior was observed for each structure. Remarkably, 24CPhCz, having the strongest intermolecular interaction between carbazole units exhibited the most impressive UOP with a long lifetime of 1.06 s and a phosphorescence quantum yield of 2.5 %. 34CPhCz showed dual‐emission UOP and thermally activated delayed fluorescence (TADF) with a moderately decreased phosphorescence lifetime of 770 ms, while 35CPhCz only displayed TADF owing to the absence of strong electronic coupling between triplet chromophores. This study provides an explanation for UOP generation in crystal and new guidelines for obtaining UOP materials. Abstract : Ultralange organische Phosphoreszenz (UOP) kann über die Stapelung der Triplettchromophore im Kristall gesteuert werden. Je stärker die Interaktion zwischen den Carbazolchromophoren ist, umso bevorzugter ist die Generierung der UOP (siehe 24CPhCz und 34CPhCz im Bild). Schwächere Wechselwirkungen zwischen den Triplettchromophoren, begleitet von starken Wechselwirkungen zwischen Benzoleinheiten, führen zum Verschwinden der UOP und zum Auftreten einer thermisch aktivierten verzögerten Fluoreszenz (35CPhCz).